Formulation and evaluation of an automatic dishwashing detergent using local enzymes - Naganthran, Ashwini (2017)
Due to the concern towards the environment, the detergent industry changed their approach to a more environmental friendly, which includes biodegradable chemicals and enzymes. Hence, a locally isolated enzyme, T1 lipase was used to formulate an automatic dishwashing detergent,however the efficiency in the hard water was very low. Consequently, enzymes such as Rand protease and maltogenic amylase were incorporated to formulate a new automatic dishwashing detergent with a better efficiency. All three enzymes have been studied, produced and evaluated for automatic dishwashing detergent (ADD) formulation. Lipase, protease and amylasewere isolated from Geobacillus zalihae strain T1, Bacillus subtilis strain Rand, and Geobacillus sp. SK70, respectively and all are thermophilic enzymes. These enzymes were produced in shake flask scale and the enzymatic activities were assayed. Compatibility tests of these enzymes with different detergent components were carried out. These enzymes were mostly stable in nonionic surfactants, especially those that are made of polyhydric alcohols. All enzymes were also stable in a mixture of sodium carbonate and glycine, at pH 9.25. These enzymes are also stable in sodium citrate. Each free enzyme was evaluated for its highest performance and the amount of enzymes to reach the significant performance was noted and used in detergentformulation. The dishwashing performance of the formulated ADDs was evaluated in term of percent soil removed using the Leenert‘s Improved Detergency Tester. Formulated detergent consists of alkyl polyglucoside (7%) , sodium bicarbonate (3%), polyacrylate (5%), sodium citrate (3%) containing the lipase, protease, amylase. The pH was adjusted using glycine which is approximately 7%. T1 lipase was then spray-dried whereas Rand protease and maltogenic amylase were freeze dried using additives. The addition of three different enzymes did improve the dishwashing efficiency in both soft and hard water. Detergent with encapsulated enzymes showed a better washing than free enzymes in both soft water and hard water. In 350ppm CaCO3, the maximum dishwashing performance was achieved at 20 and 30 minutes of washing using free and encapsulated enzymes respectively. The washing efficiency of formulated detergent containing enzymes was proven better than previous detergent formulation in both soft and hard water. In additiom, performance of these formulated detergents is as efficient as commercial detergent, Finish® at 50 °C. In conclusion, the best working conditions for both formulated detergents are 50 °C and 1.5% detergent concentration. In addition, detergent containing encapsulated enzymes has higher washing efficiency compared to detergent containing free enzymes in most conditions. Futhermore, these detergents should be considered to make it into powder form for a longer storage.